A CUNARD STEAMSHIP COMPANY szerepe a fiumei kivándorlásban (1902–1914): THE ROLE OF THE CUNARD STEAMSHIP COMPANY OF THE EMIGRATION IN FIUME (1902–1914) - Pelles, Márton (Közép-Európai Közlemények, 2020)
The great emigration in Fiume between 1902 and 1914 still a hot topic in the works of the domestic and foreign researchers. In those times hundred thousand people started their journey from all over Austria-Hungary to Fiume, where they could board on the Cunard ships, whiches took them to the New World. As we known these people did not start by their own ideas, but many emigration agencies promoted them to begin their ways to the “promised land with milk and honey”. This great mass of people in the first years shocked the local capacities like food, and accommodation in Fiume. Because of this the Governor of the town started to build an Emigration House for them with the aid of the Hungarian State. In my paper based on my researches in the Državni Arhiv u Rijeci (the State Archives of Rijeka), and the newest Croatian and Hungarian literature I will present how the Hungarian State has built a whole new industry in Fiume to serve the emigrants, from the accommodation trough the feeding to the travelling. I also wish to mention what was like the weekdays of the emigrants in these years on the ships based on the remained reports from the officers of the Hungarian Royal Maritime Office’s. From my work I look forward that with these new sources I could enlighten the history of this great emigration from Fiume to New York.